Vitis vinifera juice ameliorates depression-like behavior in mice by modulating biogenic amine neurotransmitters (Bangladesh Journal of Pharmacology, 2015)
The advantageous effects of Vitis vinifera juice on depressive model mice were examined utilizing a blend of behavioral evaluations and biogenic amine neurotransmitter estimations. During the behavioral evaluations, immobility time on the forced swimming test and tail suspension test were measured in unstressed and immobilization-induced stressed mice. V. vinifera juice (4 mL/kg and 8 mL/kg) and fluoxetine (20 mg/kg) produced a significant decrease in immobility time of both unstressed and stressed mice when compared with their respective saline-treated control groups in both paradigms. Neurotransmitters were measured using high-performance liquid chromatography with electrochemical detector. V. vinifera juice raised the levels of both serotonin (p